Genomic Characterization of a Coxsackievirus A20 Strain Recovered from a Child with Acute Flaccid Paralysis in Nigeria (2020)
In light of recurrent outbreaks of circulating vaccine-derived poliovirus 2 (cVDPV2) in Nigeria, we describe the genome sequence of a coxsackievirus A20 strain (CVA20). The nonstructural region (NSR) of this CVA20 genome showed that the enigmatic NSRs in recombinant cVDPV2s (GenBank accession numbers JX275140and KX162716) found in Nigeria were from indigenous enterovirus species Cs (EV-Cs).